Rancang Bangun Aplikasi Sistem Antrean di Poliklinik Penyakit Dalam - Yosep Septiana; Wiyoga Baswardono; Moch Renaldi Rismawan (Institut Teknologi Garut, 2023)
Polyclinic is a health facility for health services, which consists of basic medical or specialist medical. In a polyclinic there is a media queue as the serial number of the patient from the first to the last. In processing the queue still uses paper, with an average number of patients who come as many as 10 to 15 people per day the queue process takes quite a long time, this sometimes makes patients complain because the queue and registration process is quite time consuming. The purpose of this study is to create a queuing system that can make it easier for patients and staff at the polyclinic, with a queuing system that can provide smoothness and convenience in handling queues. In compiling this research for data collection conducting observations, interviews, and queuing system applications using the Rational Unified Process (RUP) method. This method has four phases, namely inception, elaboration, construction, and transition, where modeling is using the Unified Modeling Language (UML), while for making applications using Python and MySQL as databases. In the end, this research resulted in a queuing system application that can be accessed via an online web browser. This application is expected to help the internal medicine polyclinic at the Tk hospital. IV. 03.07.04 Guntur to minimize piles of patient queues.